2010
DOI: 10.1021/ja103828f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Shape Control of CuInS2 Nanoparticles

Abstract: Cu(2)S-CuInS(2) hybrid nanostructures as well as pure CuInS(2) (CIS) nanocrystals were synthesized by methods of colloidal chemistry. The structure, the shape and the composition of these nanomaterials were investigated with transmission electron microscopy (TEM), powder X-ray diffraction (XRD) and energy dispersive X-ray analysis (EDX). By changing the reaction conditions, CuInS(2) nanorods with different aspect ratio, dimeric nanorods as well as hexagonal discs and P-shaped particles could be synthesized. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
317
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 282 publications
(339 citation statements)
references
References 41 publications
20
317
2
Order By: Relevance
“…In agreement with previous reports, ZnS shell improved the intensity of absorption and emission [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. The dependence of the PL intensity was no more monotonic; for example, it exhibited a maximum at the synthesis time of about 60 min with improved QY of 65.5%.…”
Section: Shell Synthesissupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous reports, ZnS shell improved the intensity of absorption and emission [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. The dependence of the PL intensity was no more monotonic; for example, it exhibited a maximum at the synthesis time of about 60 min with improved QY of 65.5%.…”
Section: Shell Synthesissupporting
confidence: 92%
“…CIS or CIS/ZnS QDs with spherical, triangle, rod-like, hexagonal, and spindle shapes were synthesized using different ligands such as TOP, oleylamine (OLA), DDT, DMF, OA, and trioctylphosphic oxide (TOPO) [22][23][24][25][26][27][28][29][30][31][32]. Until now, the PL QYs of CIS/ZnS in the reach stage have been up to more than 80% [24,25,27,33].…”
Section: Introductionmentioning
confidence: 99%
“…reaction time and temperature). In the case of CuInS 2 colloidal synthesis, CuInS 2 and oleylamine, trioctylphosphine oxide (TOPO), was injected in a mixture by 1-dodecanethiol, tert-dodecanethiol [11]. This solution was maintained at 240 o C, resulting in the formation of elongated CIS nanoparticles that had approximately uniform size distribution.…”
Section: Cuins 2 (Cis) Nanocrystalsmentioning
confidence: 99%
“…It was observed that 75 seconds after injection, nanoparticles size increased, resulting in a squarelike shape ( Figure 2). After 80 seconds, the CIS particles reached an elongated shape, which then increased along the (002) axis and had an orientations perpendicular to the axis (100) [11]. CIS elongated shape had an optical absorption between 400 nm and 900 nm.…”
Section: Cuins 2 (Cis) Nanocrystalsmentioning
confidence: 99%
“…It has been shown by the Banin group [1] that the heterogeneous growth behaviour of gold nanocrystals on nanorods is significantly different for different cadmium chalcogenides, such as CdSe and CdS [1]. We applied CuInS 2 NPs, synthesized according to a method described previously [23], in order to find out, whether a selective growth of gold nanocrystals is also possible on other I-III-VI NPs. In this reaction, the growth behaviour of gold is different.…”
Section: Hybrid Nanostructuresmentioning
confidence: 99%